Efficacy of Indigenous Bacteria in the Biodegradation of Hydrocarbons Isolated from Agricultural Soils in Huamachuco, Peru - Claudio Quiñones-Cerna; Alina Castañeda-Aspajo; Marycielo Tirado-Gutierrez; David Salirrosas-Fernández; Juan Carlos Rodríguez-Soto; José Alfredo Cruz-Monzón; Fernando Hurtado-Butrón; Wilmer Ugarte-López; Mayra Gutiérrez-Araujo; Medardo Alberto Quezada-Alvarez; Julieta Alessandra Gálvez-Rivera; Mario Esparza-Mantilla (Microorganisms)
Pollution from crude oil and its derivatives poses a serious threat to human health and ecosystems, with accidental spills causing substantial damage. Biodegradation, using microorganisms to break down these contaminants, presents a promising and cost-effective solution. Exploring and utilizing new bacterial strains from underexplored habitats could improve remediation efforts at contaminated sites. This study aimed to evaluate the hydrocarbon biodegradation capacity of bacteria isolated from agricultural soils in Huamachuco, Peru. Soil samples from Oca crops were collected and bacteria were isolated. Biodegradation assays were conducted using diesel as the sole carbon source in the Bushnell Haas Mineral medium. Molecular characterization of the 16S rRNA gene identified four strains. Diesel biodegradation assays at 1% concentration were performed under agitation conditions at 150 rpm and 30 °C, and monitored on day 10 by measuring cellular biomass (OD600), with hydrocarbons analyzed by gas chromatography. The results showed Pseudomonas protegens (PROM2) achieved the highest efficiency in removing total hydrocarbons (91.5 ± 0.7%). Additionally, Pseudomonas citri PROM3 and Acinetobacter guillouiae ClyRoM5 also demonstrated high capacity in removing several individual hydrocarbons. Indigenous bacteria from uncontaminated agricultural soils present a high potential for hydrocarbon bioremediation, offering an ecological and effective solution for soil decontamination.